Variáveis contingenciais e sistemas de controle gerencial: uma investigação nos supermercados paraibanos - Aires, Matheus de Farias (2022)
In detriment of the corporate uncertainties imposed by the current market, it is evident that the decision making process of an organization is a complex routine and must consider a large number of variables to mitigate such uncertainties and direct the best decision making. In this process, the Management Control System (MCS) is conceptualized as a tool capable of guiding the strategic decision through the interpretation of available information. The contingency theory proposes that an organization is inserted in an environment, and thus, is in constant interaction with the contingential variables inherent to this location. In view of this, the objective of this study was to analyze the association of contingential variables with the Management Control Systems in supermarkets in Paraiba. It is a quantitative study, of the survey type, which made use of a questionnaire as an instrument of information collection, presenting a reliability test of the collected data of 95.8%. The study was developed from two groups of the same population, the first consisting of supermarkets in Paraíba associated with a chain, and the second consisting of establishments not associated with a chain. The contingency variables studied in this research are: environmental uncertainty, technology, strategy, structure and size, and the SCG variables were: innovative organic culture, formal controls and strategy for differentiating competitors. Regarding data analysis procedures, descriptive statistics techniques were used, mainly to achieve the first specific objective, in addition to Spearman correlation analysis, Mann-Whitney U test, cluster analysis, multidimensional scaling and factor analysis to achieve the general objective, as well as the other specific ones. The results of this research state that the most adopted practices by supermarkets regarding the SCG are the following: i) differentiation by offering products at a lower selling price than competitors; ii) achieve the lowest cost; iii) offer a better mix of products; iv) cost control; v) control of the practiced margins; vi) take advantage of opportunities quickly; and vii) enable informal access to superiors.